Effect of Host and Kind of Oil on Some Nutrition Parameters of Trogoderma granarium Everts Larvae . - Batool A. Karso; Al-malaah N.M (Mesopotamia Journal of Agriculture)
The results of studying the effect of host kind and kindy of oil on some nutrition parameters of Trogoderma granarium Everts Larvae showed a significant variation on nutrition parameters according to the host and kind of oil . The Sunflower oil exhibited a highest percentage of food consumption reached 99.3 % and zero starvation percentage and 5 mg. seed consumed per Larvae from Sunflower , as compared to 72.25, 27.74 and 3.61 mg/ seeds/ larva respectively for those reared up on wheat and treated with the same oil. When the other oils were variation in effects on the nutrition parameters and Almond oil exhibit a highest percentage of starvation, mean average for starvation reached 90 % .